Penerapan Metode Mind Mapping Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Kelas III MI Tarbiyatul Ulum Pengampon Menganti Gresik - Nur Hayya Romadhoni; Nurul Agustin; Ria Resti Fauziah; Rahmat Rudianto; Ainul Fithriyah (InsightEd, 2026)
This study aimed to improve the creative thinking ability of third-grade students at MI Tarbiyatul Ulum Pengampon Menganti Gresik through the implementation of the Mind Mapping method. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 20 third-grade students. Data were collected through observations of teacher and student activities, creative thinking tests, interviews, and documentation. Data analysis was carried out using qualitative descriptive and quantitative techniques. The results showed an improvement in teacher activity from 60.2% in Cycle I to 82.0% in Cycle II, and student activity increased from 52.7% to 82.3%. In addition, students’ creative thinking abilities—covering fluency, flexibility, originality, and elaboration—also improved significantly in Cycle II. These findings indicate that Mind Mapping effectively helps students organize information visually, understand conceptual relationships, and develop ideas more creatively. Therefore, the Mind Mapping method is appropriate as an innovative learning strategy to enhance creative thinking skills among lower-grade students in Islamic elementary schools.